The effect of using lighting design and color correction in highlighting the dramatic meaning - Mohamed Hussein Ahmed ammar; SAFWAT ABOTAWILLA; Wael mohamed Anany (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
Lighting design and color correction are one of the means of artistic formation that highlights a wide range of meanings that any artwork aspires to communicate its goals, or in a more accurate sense, and transform the writing represented in the paper script into a set of feelings and feelings within the recipient of the artwork, which in turn is one of the most important goals Artwork, the successful artwork is the one that can invade the human soul and make it in a state of unity with the main idea of the artwork.The role of the successful director of photography is no longer reductive in drawing the light of the scene only, but it has become the duty of his readers to work well and study it and know its dimensions and the goals he wants to communicate from turning that literary work into a dramatic work so that he can put an appropriate design for the picture in terms of lighting and color composition.The lighting design within the dramatic work is like the dramatic code of the artwork. Through the lighting design, whether it is the angle of lighting or the optical layer, we can begin to decipher the data of the dramatic work, and the recipient can begin to enter into the depths of the artwork